2023
DOI: 10.14716/ijtech.v14i1.5454
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Electric Motorcycle in Improving Personal Sustainable Economy: A View from Indonesia Online Ride-Hailing Rider

Abstract: The energy cost of electric vehicles is reportedly less than its internal combustion engine counterpart due to using technologies to boost efficiency through regenerative braking. Based on this condition, a possibility of its implementation as vehicles in ride-sharing applications is observed. Therefore, this study aims to analyze the benefits of electric vehicle implementation to ride-sharing platforms in Indonesia. An electric motorcycle was used in this study as a vehicle for daily ride-sharing activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The results showed that 45.7% of EM users preferred charging for less than 1 hour, while for EM non-users, the most popular choice was 1-2 hours (51.2%). However, the average charging time for batteries in Indonesia is around 3-4 hours or more, which means that the existing charging facilities in the country have not met the community's preferences [25]. Specifically, EM users prefer a charging duration below 1 hour, which may relate to their experience using and operating EM.…”
Section: Technical Preferencesmentioning
confidence: 99%
“…The results showed that 45.7% of EM users preferred charging for less than 1 hour, while for EM non-users, the most popular choice was 1-2 hours (51.2%). However, the average charging time for batteries in Indonesia is around 3-4 hours or more, which means that the existing charging facilities in the country have not met the community's preferences [25]. Specifically, EM users prefer a charging duration below 1 hour, which may relate to their experience using and operating EM.…”
Section: Technical Preferencesmentioning
confidence: 99%
“…Sustainable development depicted smart cities and integration of the Internet of Things (IoT); for instance, drones that operate autonomously or semi-autonomous are supported by artificial intelligence like machine learning (ML) and Deep Learning (DL) has demonstrated an increase in the market arena (Berawi, 2023;Shafik et al, 2020a). Proper resource utilization and allocation using the existing technologies are prevailing, like using electric motorcycles to reduce environmental pollution (Suwignjo et al, 2023) and social benefit-cost assessments (Sarkar, Sheth, and Ranganath, 2023). The future unmanned aerial vehicle (UAV) projection plans boost UAV-networked communication productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Promoting environment-friendly transportation systems is essential to prevent catastrophes (Suwartha et al, 2021), especially in Malaysia, where transportation accounts for 30% of energy consumption (Ministry of Transportation Malaysia, 2017). Thus, electric cars are promoted as an efficient option for their ability to operate partially or fully on electric motors and hence consume little to zero fossil fuels in addition to total ownership cost advantages as compared to conventional vehicles (Suwignjo et al, 2023). In the past years, the Malaysian government has encouraged the usage of electric cars by introducing several policies, including the subsidization of electric car sales.…”
Section: Introductionmentioning
confidence: 99%